CROSS-COUNTRY ANALYSIS ON NEIGHBORING MIGRATION POLICY BY THE EXAMPLE OF FINLAND AND RUSSIA - Maria, Pitukhina; Přívara, Andrej (Proceedings of the International Conference on Education, 2017)
Article deals with, in particular, migration influence on both qualitative and quantitative human capital parameters in a recipient country. Currently Russian migration policy is under transition - the necessity of taking serious measures is acute, especially taking into account migrants’ human capital parameters such as education. Tajikistan, Kirgizia, Armenia are main countries of migrants’ origins in Russia. Migrants from these countries are mainly unskilled, poorly educated, low wage labor. Migration policy in Finland is considered to be highly adaptive and balanced. Reasons for Finland’s success are the best European projection system of labour market parameters; VET and higher education development; skills anticipation; information dissemination in society; lifelong learning implementation. There is a variety of methods widely applied in the article – qualitative evaluation of labour market parameters, desk studies, documents analysis, and comparative research. The research reflects on the OECD indicators “Education at Glance” 2011; Statistics Russia; Russian Strategy 2020 – a new model of growth; National Finnish Acts 1994, 1999, 2003, 2004; Concept on state migration policy in Russia till 2025; EUROSTAT etc. Authors conclude that Russian migration policy shall implement Finnish approach since only full and up-todate data will contribute to the result-oriented decision-making process.